Self-reported playing preferences resonate with emotion-related physiological reactions during playing and watching of first-person shooter videogames. Issue 155 (November 2021) - Holm, Suvi K.; Kaakinen, Johanna K.; Forsström, Santtu; Surakka, Veikko
Abstract: The present aim was to investigate emotion-related physiological responses and subjective ratings of two groups of active gamers (N = 24) in response to both playing and watching a video of a first-person shooter game. Participants of one group had high preferences for game dynamics in first-person shooter games, whereas the other group disliked such dynamics. Electrodermal activity (EDA), heart rate (HR), and electromyographic (EMG) activity of the corrugator supercilii (i.e., brow furrowing) and the zygomaticus major (i.e., smiling) muscles were measured while playing and watching a gameplay video. After the playing and watching sessions, the participants rated their experienced level of valence and arousal. The results showed that those who liked the game dynamics showed comparable and stable levels of EDA and HR during both playing and watching. Those who disliked the game dynamics showed overall higher levels of EDA and HR during playing than watching a video, and a rising EDA tendency especially during watching a video. Playing evoked overall higher corrugator supercilii activity than watching in both groups. The group that liked the game dynamics showed a steep EMG increase in the activity of the corrugator supercilii, whereas the group that disliked the game dynamics showed less EMG increase. As for ratings of valence and arousal, both groups reported more positive valence and higher arousal after playing than after watching a video, and there were no differences between the groups. In sum, the results showed that player preferences were associated with players' emotion-related physiological responses. The results also showed that playing as opposed to watching generated higher autonomic arousal, but only for players who disliked the dynamics of the game.